Factors Contributing To Stress on House Officers during Covid-19 Pandemic in the District and State Hospitals of Negeri Sembilan, Malaysia - Purushothaman, Ramalingam (2024)
This study examined the psychological effects of the Covid-19 pandemic on house officers in district and state hospitals in Negeri Sembilan, Malaysia, revealing significant challenges faced by these frontline healthcare workers. The objective was to elucidate their stressors and identify determinants of stress, aiming to provide insights that could improve their well-being. The present study conducted between May and August 2023, the cross-sectional questionnaire survey gathered responses from 208 house officers via an online platform, adhering to social distancing measures. A comprehensive review of databases such as Google Scholar, Embase, PubMed, and Library was performed, focusing on English language publications, cross sectional studies, and reports on psychological issues like depression, anxiety, and stress. The sample size calculation ensured representativeness, and Pearson’s correlation coefficient was used to analyze inter-correlations between variables. The findings revealed a significant deterioration in the psychological well-being of house officers, with increased stress leading to higher cases of anxiety and burnout. These results underscored the urgent need for support measures to address mental health challenges. Practical implications highlighted the necessity for accessible counseling services and effective measures to safeguard the mental well-being of house officers. By identifying the determinants of stress, the study offered insights that could help reduce stress levels and improve overall well-being during crises. The research emphasized the broader social impact of supporting frontline healthcare workers' mental health, which is critical for maintaining an effective healthcare system, especially during public health crises. Addressing these mental health challenges could lead to better patient care and overall public health outcomes. This study provided valuable insights into the specific challenges faced by house officers in Negeri Sembilan during the Covid-19 pandemic, contributing to the literature by highlighting the need for targeted mental health interventions.